Teoria do coalescente e Computação Bayesiana aproximada como ferramentas para resolver questões da genética de populaçõeslatino-americanas - Mateus Henrique Gouveia (2013)
In this study we used the coalescent theory and a new statistical methodology known as Approximate Bayesian Computation - ABC to simulate genetic data and to infer demographic parameters associated with the history of Latin American populations. We used ten neutralregions previously selected by Frisse, 2001 specifically to study human demographic history. We used the population-genetic model previously studied by Dr. Marilia Scliar of population divergence followed by gene flow between two populations of native Peruvian Andes (Quechuas) and Selva Alta Amazon (Shimaas), in which we added a recombinationparameter and a new informative statistic to study the divergence time among populations. We also used the Quechuas and Shimaas to study a more complex model of American peopling by Siberian populations and divergence between Native American populations. Furthermore, we simulated genetic data from populations with a demographic history compatible with the formation of Latin American admixed populations, which will allow us testing genetic hypotheses in the context of Epigen project. In the two demographic models proposed we found a divergence time less than 5000 years between the Quechua and Shimaa populations, what suggests that the separation between these populations occurred after the colonization of America. Finally, we estimated most likely time of American peopling of around 22,000 years and a founder effective number about 400 individuals.